Type 1 Diabetes Mellitus and Host-Bacterial Interactions in the Oral Cavity - Gürsoy, Ulvi Kahraman; Yilmaz, Neslihan; Yilmaz, Dogukan; Grönroos, Sanni; Gürsoy, Mervi (Elsevier, 2025)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease which is characterized by the destruction of insulin producing pancreatic β-cells. Current evidence supports the contribution of T-cells, macrophages, B-cells, and dendritic cells to the pathogenesis of T1DM as well. T1DM-associated risk factors, including defects in host immune response, socioeconomic conditions and environmental factors create dysbiotic environment in the oral cavity, which support the growth of pathogenic microbial biofilms. Changes in microbial composition, together with the diminished immune response, lead to the development of two most common oral diseases, caries and periodontal diseases. In the present review, we summarized the current evidence on oral manifestations of T1DM, and described the shifts in oral microbial composition and oral immune response.